The role of Arabs in the Trade and Economic Life in Society Surakarta - Retna Murtiningsih (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The role of the Arab / Encik in the world economy has been felt since decades ago.This is closely related to the identity of an entrepreneur in the field of economy . Inaddition, the context of socio-cultural and political interactions participate cultivate anArab identity/ Encik in Surakarta . It thus may be either positive or negative for aparticular community. As an example application on ethnic interaction in Surakarta ,completes this contextual thinking . Projections for overcoming the task together coverall aspects of the nation's economy between people and government .Keywords : trade , economic activities , market. Arab/Encik, Indigenous , globalization .